Comparing the growth of under ‎‏2‏‎ years old children referring to health centers of ‎Bandar Abbas with NCHS standard curve - kazem hoseinzadeh; asyeh por mehr; roghayeh rahmati; hadi yosefi (Guilan University of Medical Sciences, 2005)
Introduction: Assessing the growth and development of children is an important parameter in ‎their health assessment. Since the growth effecting agents vary in countries, it is not sensible ‎considering a unique growth chart for all.‎ Objective: In this research we have studied the growth chart of children under ‎‏2‏‎ years old in ‎BandarAbbas and compared it to standard NCHS growth curve.‎ Methods: In this descriptive study, we have selected ‎‏1000‏‎ children from five health centers ‎of BandarAbbas by means of simple randomized sampling. All data about children (height & ‎weight) and their parents characteristics such as education and job were gathered and ‎analyzed by means of t-test and ANOVA.‎ Results: In contrary to height curve, the weight curve of children was below the standard ‎level. A significant relationship has been observed between weight curve and parents ‎education and fathers job, but mothers job does not have a significant effect on children ‎growth chart.‎ Conclusion: The weight gain pattern of children up to ‎‏24‏‎ months in Bandar Abbas differs ‎from the standard and this difference widens in age ‎‏6-18‏‎ months and is affected by factors ‎such as parents education and fathers job. Therefore, in attention to same timing of ‎introduction of solid food and tooth budding with widening of children weight curve with ‎standard curve, (all happens in ‎‏6‏‎ months age),more attention should be paid to feeding and ‎proper health intervention to be conducted in order to control effective factors on children ‎development.‎